2015
DOI: 10.1017/s1431927615000768
|View full text |Cite
|
Sign up to set email alerts
|

Bone Diagenesis and its Implication for Disease Diagnosis: The Relevance of Bone Microstructure Analysis for the Study of Past Human Remains

Abstract: When bone is exposed to the burial environment it may experience structural changes induced by multiple agents. The study of postmortem alterations is important to differentiate decomposition phenomena from normal physiological processes or pathological lesions, as well as to assess bone tissue quality. Microscopy is of great utility to evaluate the integrity of bone microstructure and it provides significant data on long-term bone decomposition. A total of 18 human bone sections (eight archeological and ten r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In cariology research, the adverse effect of acidic pH on tooth dissolution caused by oral bacteria has been clearly demonstrated [19]. The correlation between low or acidic pH levels and adverse effects on bone health has also been previously established; however, data from bone diagenesis research indicates that higher or basic pH values can have damaging effects on bone health [12]. We also observed such a phenomenon in our previous study, and found that both acidic and basic environments produced by bacteria were still associated with HA damage [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cariology research, the adverse effect of acidic pH on tooth dissolution caused by oral bacteria has been clearly demonstrated [19]. The correlation between low or acidic pH levels and adverse effects on bone health has also been previously established; however, data from bone diagenesis research indicates that higher or basic pH values can have damaging effects on bone health [12]. We also observed such a phenomenon in our previous study, and found that both acidic and basic environments produced by bacteria were still associated with HA damage [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recent insight into bone diagenesis gained from the fields of paleoecology and paleopathology further demonstrate the importance of direct microbial degradation of hard tissues, i.e. bone and teeth [12]. Bone diagenesis has been shown to be a complex and site-specific process; and it is dependent on various external features of the burial environment such as pH, temperature, presence of oxygen, soil composition, groundwater chemistry, and most prominently, microbial-induced bioerosion [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following inhumation, bone structural changes (including destruction of histological integrity or bioerosion) consist of a multiphase process involving alteration of the organic fraction of the bone matrix, changes to the mineral component (hydroxyapatite) and mineral infilling of vascular spaces [22,23]. Briefly, these structural changes may affect the integrity of the structural bone matrix, osteocytes and endothelial cells [10,24]. In general terms, buried skeletons may be considered to follow a…”
Section: General Changes In Bones After Burialmentioning
confidence: 99%
“…3 "diagenetic trajectory" through time, the expression of which has increasingly been used to describe various degradation pathways that bones may follow under the influence of various environmental factors-such as temperature, pH [21,25], local microbial fauna, hydrology [21,[26][27][28][29][30][31][32] and method of burial [24]. As a result of diagenesis, buried bones present a loss of bone matrix, frequently described as 'canals' or 'tunnels', caused by microorganisms or environment [10,33].…”
Section: Fsi _2018mentioning
confidence: 99%